Genome Organization and Adaptive Potential of Archetypal Organophosphate Degrading Sphingobium fuliginis ATCC 27551. (27th August 2019) - Azam, Sarwar; Parthasarathy, Sunil; Singh, Chhaya; Kumar, Shakti; Siddavattam, Dayananda
Abstract: Sphingobium fuliginis ATCC 27551, previously classified as Flavobacterium sp. ATCC 27551, degrades neurotoxic organophosphate insecticides and nerve agents through the activity of a membrane-associated organophosphate hydrolase. This study was designed to determine the complete genome sequence of S. fuliginis ATCC 27551 to unravel its degradative potential and adaptability to harsh environments. The 5, 414, 624 bp genome with a GC content of 64.4% is distributed between two chromosomes and four plasmids and encodes 5, 557 proteins. Of the four plasmids, designated as pSF1, pSF2, pSF3, and pSF4, only two (pSF1 and pSF2) are self-transmissible and contained the complete genetic repertoire for a T4SS. The other two plasmids (pSF3 and pSF4) are mobilizable and both showed the presence of an oriT and relaxase-encoding sequences. The sequence of plasmid pSF3 coincided with the previously determined sequence of pPDL2 and included an opd gene encoding organophosphate hydrolase as a part of the mobile element. About 15, 455 orthologous clusters were identified from among the cumulatively annotated genes of 49 Sphingobium species. Phylogenetic analysis done using the core genome consisting of 802 orthologous clusters revealed a close relationship between S. fuliginis ATCC 27551 and bacteria capable of degradation of polyaromatic hydrocarbon compounds. Genes coding for transposases, efflux pumps conferring resistance to heavy metals, and TonR-type outer membrane receptors are selectively enriched in the genome of S. fuliginis ATCC 27551 and appear to contribute to the adaptive potential of the organism to challenging and harsh environments.